Um modelo de simulação de sistemas aplicado à programação da produção de um frigorífico de peixe - Pereira, Carla Roberta (Universidade Federal de São Carlos, 2011)
The necessity for making production processes more efficient and effective is the desire of any organization. For this to become reality and does not generate high investment is necessary to use techniques that assist in improvement of the production process along with a appropriate schedule of productive resources. Among these techniques, the Simulation assists effectively those improvements, because it seeks to import the reality for a controlled environment, under several conditions, without physical risks and/or high costs involved. This technique becomes even more useful in growing markets, such as the tilapiculture. With the emergence of new fish processing facility, it is necessary a better organization in order to produce more adequately, serving its clients satisfactorily and expanding its business. Thus, the main purpose of this study was to develop a simulation model to assist the decision making about the production scheduling of a fish processing facility, located in the Sao Paulo state. To this end, it used as computational tool the software Arena, by Rockwell Software, and as research method the modeling and simulation, including in this the methodology SimuCAD and the development phases of a simulation model discussed by Banks (1998) and Law and Kelton (2000). With the construction of the model was able to work several alternative scenarios, testing different working hours, types of flows and production capacity, besides variations of the ending inventory in relation to sales. As result, it obtained a useful and differentiated model simulation to assist the decision making about production scheduling of fish processing facility studied, besides reducing the lead-time process and attending all the specific objectives established. At the end of this study, proposals for future research were suggested.
Keywords: Simulação; Programação da produção; Frigoríficos; Tilapicultura; Sistemas de produção; Frigorífico de peixe; Software Arena; Simulation; Production scheduling; Fish processing facility; Tilapiculture; Production systems; Software Arena; ENGENHARIAS::ENGENHARIA DE PRODUCAO